New technique of end to side two layered and stented duct to mucosa pancreaticojejunostomy with omental wrapping during Whipple operation - Hesham A. Elmeligy; Ahmed M. Azzam; Yousra Ossama; Mahmoud Rady (BMC Surgery)
Abstract Background A leaking pancreaticojejunal anastomosis is typically the cause of major problems following pancreaticoduodenectomy. To stop fistula formation, omental flaps were positioned around the pancreaticojejunal anastomosis. Methods Forty-eight individuals who had pancreaticoduodenectomy procedures performed between March 2022 and March 2024 were examined. Based on the placement of a stent and omental flaps around the pancreaticojejunal anastomosis, the patients were split into two groups: group A, consisting of twenty-four patients, did not get omental wrapping and stenting, and group B, consisting of twenty-four patients, received omental wrapping with stent inside the pancreaticojejunal anastomosis. To evaluate the efficacy of the omental flap operation in preventing postoperative pancreatic fistula and other complications, perioperative data from both groups was examined. Results There were no discernible variations in the clinical traits of the two groups. Group B experienced considerably lower occurrences of postoperative pancreatic fistula (20.8% vs. 4.2%), post-pancreatectomy hemorrhage (4.2% vs. 0%), biliary fistula (4.2% vs. 0%), and delayed gastric emptying (12.5% vs. 4.2%). Group B had a considerably lower overall morbidity rate (41.7% vs. 8.3%) and shorter hospital stay (15.3 vs. 10.9 days) than to group A. Conclusion Following pancreaticoduodenectomy, pancreatic stent and omental flaps around the pancreatic anastomosis can lower the risk of postoperative pancreatic fistula, post-pancrectomy bleeding, and delayed gastric emptying. This straightforward and efficient treatment can decrease the overall morbidity following pancreaticoduodenectomy. Trial registration The trial registration was recorded as ClinicalTrial.gov Identifier No.: NCT06630910 on 10/05/2024. Our study also adheres to the Declaration of Helsinki.